Partnership of obstetrician and neonatologist to improve neonatal outcome in peri-viable and premature babies: a cross sectional survey - Patankar, Ujjwala S.; Patankar, Sameer U.; Sonak, Mangala; Patil, Rashmi; Upadhye, Aditi J.; Upadhya, Jayshree J (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Collaboration between obstetricians and paediatricians/Neonatologists provides the best quality care to infants and their mothers. Present study was conducted to evaluate the practices of obstetricians and neonatologists’ partnership to improve neonatal outcome. Methods: Present cross-sectional, observational study was conducted on 50 Obstetricians and 50 paediatricians/ neonatologists during October 2021 to evaluate the practices of obstetricians and neonatologists’ partnership to improve neonatal outcome. Results: In present study, among 50 obstetricians and 50 pediatricians/ neonatologists, all i.e., 100 (100%) feel that partnership of obstetrician and neonatologist in managing pre-viable pregnancy improves neonatal outcome. Among 50 obstetricians, all i.e., 50 (100%) said that they will explain the need for caesarean section and if necessary classical caesarean section. All said they will explain the need and advantages of steroids. Among 50 pediatricians/ neonatologists, majority i.e., 44 (88%) said that they will explain the need for caesarean section and if necessary classical caesarean section. All said they will explain the need and advantages of steroids. Among 50 obstetricians, majority i.e., 45 (90%) said that they will explain thoroughly the risk to the baby, survival, short term complications and disability, 30 (60%) each said that they will explain thoroughly the risk of RDS, need of resuscitation, need of NICU for baby, uncertainty of hospital stay and outcome. Among 50 pediatricians/ neonatologists, all i.e., 50 (100%) each said that they will explain thoroughly the risk to the baby, survival, short term complications and disability, the risk of RDS, need of resuscitation, need of NICU for baby, uncertainty of hospital stay and outcome. Expressions of pediatricians/ neonatologists were significantly different on counselling aspects of mother and baby. Conclusions: In present study, majority of obstetricians and pediatricians/ neonatologists were of opinion that partnership between them surely improves neonatal outcome in peri viable and preterm babies.